Insertion Et Maintien Des Femmes Dans Les Groupements Associatifs En Côte d’Ivoire : Cas De La Coopérative COMAGOA-ROXY Dans La Commune d’Adjamé - Augustin, Kouadio Amani; Rosamonde, Yao; Vincent, Mouroufie Kouassi Kouman (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the strategies put in place by women to integrate and to maintain themselves in the activities of sale within the cooperative. In doing so, we rely, on the one hand, on the qualitative approach through the individual interviews with the Co-operative Comagoa ROXY at the Gouro market and the town hall of Adjamé. This was together with a focus group that brought together the few women members of the Cooperative. On the other hand, it was done using a quantitative approach through a questionnaire to co-operators of Comagoa ROXI. In total, the study revealed the mobilization by women of social capital as a strategy of insertion and maintenance in the cooperative. In the same way, the financial power of these women allows them to gain privileged positions while guaranteeing their maintenance within the cooperative.